Ecosystem services in the water-energy-food nexus - Bekchanov, Maksud; Ringler, Claudia; Mueller, M. (Walter de Gruyter GmbH, 2015)
Given their substantial societal benefits, such as supporting economic activities and providing better livelihoods in rural areas, ecosystem services should gain higher importance in water-food-energy nexus debates. Yet, not all values from ecosystems are quantifiable, data is often not adequate and methods of measuring these values are not sound. This situation challenges researchers and water managers to improve research tools and give adequate attention to ecosystem services by implementing interdisciplinary approaches and integrated management of ecosystems and their services.